Somalia a state of need - Hannan, Lucy; Integrated Regional Information Networks; LC Gift Collection (Library of Congress) ([Nairobi : IRIN, 2006)
After years of conflict and isolation, Somalia finds itself once mor e on the brink. Much of the country is now under the control of the Uni on of Islamic Courts, but will Somalia's new actor bring security and d evelopment or set it on the path to regional conflict?
Summary from videodisc container.
Not viewed.
Sources used: videodisc container and label; cataloging record from OvOp field office.
Camera, Walter Kigali ; edited by Trupti Shah.
In English and Somali with some English subtitles.
Keywords: Somalia -- Politics and government -- 20th century; Short films; Nonfiction films